Data equilibrium based energy-saving scheme in mobile wireless sensor networks - GAO Shuai; HUO Hong-wei; ZHANG Hong-ke; ZHANG Si-dong (Tongxin xuebao)
Aiming at dense wireless sensor networks with a path-constrained mobile sink, an optimized partition scheme of sub-sinks’ overlapping time was proposed based on data equilibrium.And a two-phase communication protocol was designed to effectively control the amount of data generated by each node through diffusion of the data equilibrium in-formation.Simulation experiments show that the proposed protocol and algorithms outperform other conventional methods in terms of data equilibrium rate, network lifetime.